2017
DOI: 10.1177/0272989x17729359
|View full text |Cite
|
Sign up to set email alerts
|

Strengths and Gaps in Physicians’ Risk Communication: A Scenario Study of the Influence of Numeracy on Cancer Screening Communication

Abstract: Most physicians know how to appropriately tailor risk communication for patients with low numeracy (i.e., with visual aids). However, physicians who themselves have low numeracy are likely to misunderstand the risks and unintentionally mislead patients by communicating incomplete information. High-quality risk communication and shared decision making can depend critically on factors that improve the risk literacy of physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
32
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 73 publications
5
32
0
4
Order By: Relevance
“…However many clinicians have been found to overestimate bene ts and underestimate harms, [60] lack ability to retrieve relevant evidence, [60] or have poor statistical numeracy and risk literacy. [66] This makes it di cult for clinicians to not only understand medical test statistics, but also to communicate this information to patients. A greater emphasis on interpretation of statistical information in medical school curricula could equip clinicians with these essential skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However many clinicians have been found to overestimate bene ts and underestimate harms, [60] lack ability to retrieve relevant evidence, [60] or have poor statistical numeracy and risk literacy. [66] This makes it di cult for clinicians to not only understand medical test statistics, but also to communicate this information to patients. A greater emphasis on interpretation of statistical information in medical school curricula could equip clinicians with these essential skills.…”
Section: Discussionmentioning
confidence: 99%
“…[38,68,[73][74][75] However, some studies demonstrated that the use of protocols resulted in inappropriate use of tests and overtesting. [28,29,66] Alber et al [43] and Bishop et al [51] found that doctors based their test ordering decisions on individual patient cases, using guidelines "as a guide rather than strict rules". [51] This resulted in variation in test ordering behaviour, with some more likely to test while others less likely.…”
Section: Guidelines Protocols and Policiesmentioning
confidence: 99%
“…Numeracy influences not only the extent to which consumers understand different risk communication formats, but also their preference for receiving quantitative information [15][16][17]. This suggests that tailoring information on the individual or average population level can increase risk communication efficiency (see [18] for an example from the medical domain). There are several validated tools that can help to adapt risk communication to individual recipients or on average to the population level.…”
mentioning
confidence: 99%
“…Conclusions. High level of education does not guarantee comprehension of risk communications as even some highly educated, experienced professionals misunderstand important risk communications in their field of expertise [18,22]. Subtle differences in risk communication formats and misunderstanding of risk statistics can have significant effects on comprehension and subsequent decisions and behavior.…”
mentioning
confidence: 99%
“…Это говорит о том, что адаптация информации на индивидуальном или популяционном уровне может повысить эффективность риск-коммуникации (см. [18], пример из медицинской области). Существует несколько проверенных инструментов, которые могут помочь адаптировать риск-коммуникации для отдельных получателей или в среднем на популяционном уровне.…”
unclassified